Toxoplasma gondii tachyzoite-extract acts as a potent immunomodulator against allergic sensitization and airway inflammation. Issue 1 (December 2017) - Drinić, Mirjana; Wagner, Angelika; Sarate, Priya; Zwicker, Christian; Korb, Elke; Loupal, Gerhard; Peschke, Roman; Joachim, Anja; Wiedermann, Ursula; Schabussova, Irma
Abstract Epidemiological and experimental studies have shown an inverse relationship between infections with certain parasites and a reduced incidence of allergic diseases. We and others have shown that infection withToxoplasma gondii prevents the development of allergy in mice. To establish whether this beneficial effect could be recapitulated by soluble products of this parasite, we tested an extract derived fromT .gondii tachyzoites. Immunization of BALB/c mice with tachyzoites lysate antigen (TLA) elicited mixed Th1/Th2 responses. When TLA was applied together with the sensitizing ovalbumin (OVA), the development of allergic airway inflammation was reduced, with decreased airway hyperresponsiveness associated with reduced peribronchial and perivascular cellular infiltration, reduced production of OVA-specific Th2 cytokines in lungs and spleens and reduced levels of serum OVA-specific IgG1 as well as IgE-dependent basophil degranulation. Of note, TLA retained its immunomodulatory properties, inducing high levels of IL-6, TNFα, IL-10 and IL-12p70 in bone marrow-derived dendritic cells after heat-inactivation or proteinase K-treatment for disruption of proteins, but not after sodium metaperiodate-treatment that degrades carbohydrate structures, suggesting that carbohydrates may play a role in immunomodulatory properties of TLA. Here we show that extracts derived from parasites may replicate the benefits of parasitic infection, offering new therapies for immune-mediated disorders.